2016
DOI: 10.1242/jeb.147884
|View full text |Cite
|
Sign up to set email alerts
|

Juveniles ofLymnaeasmart snails do not perseverate and have the capacity to form LTM

Abstract: Previously, it was concluded that the nervous systems of juvenile snails were not capable of mediating long-term memory (LTM). However, exposure and training of those juvenile snails in the presence of a predator cue significantly altered their ability to learn and form LTM. In addition, there are some strains of Lymnaea which have been identified as 'smart'. These snails form LTM significantly better than the lab-bred strain. Here, we show that juveniles of two smart snail strains not only are capable of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Juvenile W-strain L. stagnalis are unable to form LTM, but juveniles of 'smart' snails (i.e. the strains possessing enhanced memory formation) have that capability (McComb et al, 2005;Shymansky et al, 2017). However, enhanced LTM formation occurs in juvenile W-strain L. stagnalis when they detect a crayfish predator Forest et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Juvenile W-strain L. stagnalis are unable to form LTM, but juveniles of 'smart' snails (i.e. the strains possessing enhanced memory formation) have that capability (McComb et al, 2005;Shymansky et al, 2017). However, enhanced LTM formation occurs in juvenile W-strain L. stagnalis when they detect a crayfish predator Forest et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Memory-forming ability has also been shown to change across the lifespan of some L. stagnalis strains. Specifically, in L. stagnalis strains demonstrating an average memory-forming ability (both lab-bred and collected from the wild), juveniles are unable to form LTM, but this is overcome by development into adulthood (McComb et al, 2005;Shymansky et al, 2017). In addition, it has been demonstrated that the ability of the lab-bred C-strain snails to form LTM is compromised with age when they are trained with an appetitive conditioning paradigm (Hermann et al, 2007;Watson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The memory-forming ability of juvenile L. stagnalis has previously been examined in both average strains (the lab-bred C-strain as well as wild strains; McComb et al, 2005;Shymansky et al, 2017) and smart wild L. stagnalis strains . Juvenile L. stagnalis from average strains demonstrate an inability to form LTM, which is overcome by development into adulthood (McComb et al, 2005;Shymansky et al, 2017). However, juveniles from two different smart wild strains have been shown to possess the same memory-forming ability as adults from these populations.…”
Section: The Adult Transformed B-strain Still Forms Ltm When Challengmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a heritable component to the different memory-forming abilities in L. stagnalis, as the differences observed between freshly collected 'wild' strains are maintained in their lab-bred offspring (Orr et al, 2009a;Dalesman et al, 2011c;Shymansky et al, 2017). Moreover, memory enhancement, triggered, for example, by the detection of a predator, is obstructed by application of a DNA methylation inhibitor.…”
Section: Introductionmentioning
confidence: 99%